THE URGENCY OF REVISING THE REGULATIONS ON LEGAL REVIEW EFFORTS TO ACHIEVE JUSTICE AND LEGAL CERTAINTY - Resi Nurul Hasanah; Alfies Sihombing; Yeni Nuraeni (Sekolah Tinggi Ilmu Hukum Awang Long, 2026)
Law enforcement in the Indonesian rule of law, based on Pancasila and the 1945 Constitution, aims to achieve justice, legal certainty, and utility in a balanced manner. However, in practice, there are still various problems, such as the declining public trust in law enforcement agencies and inconsistencies in judicial decisions. One of the crucial problems is the regulation of the legal remedy of judicial review (PK) which still places the authority of examination and decision-making in the same institution, namely the Supreme Court, thereby potentially causing conflicts of interest and reducing the objectivity of the judiciary. This research aims to analyze the urgency of renewing the regulation of judicial review in realizing justice and legal certainty. The research method used is normative legal research with a library approach, thru the analysis of relevant primary and secondary legal materials. The research results indicate that reform of the review regulation is necessary thru the strengthening of checks and balances mechanisms, including considering the involvement of other institutions outside the Supreme Court and the reaffirmation of the novum criteria as the main requirement for submitting a review. Thus, these reforms are expected to enhance the effectiveness of the review as an instrument of justice and strengthen the integrity of the judicial system in Indonesia.